Perfil epidemiol??gico dos nascidos vivos no munic??pio de S??o Paulo, SP, entre os anos de 2004 a 2012 - Piassi, V??vian Celin (2020)
Objective: this research aimed to describe the epidemiological profile of live births of mothers living in the city of S??o Paulo / SP, from 2004 to 2012. Method: because of its descriptive, retrospective epidemiological study, a descriptive approach on secondary data registered at the Information System on Live Births (SINASC) and available on the website of the Municipal Health Secretariat of the City of S??o Paulo were used. Results: the analysis of the records of 1,555,545 newborns of mothers living in the city of S??o Paulo / SP showed that according to (Place of birth): 99.45% occurred at a hospital environment, 0.30% at home, and 0.25% at another health facility. (Maternal Age Group): 25.68% were between 25 and 29 years old; 24.34% were between 20 and 24 years old, 21.48% were between 30 and 34 years old; 13.46% were between 15 and 19 years old; 11.49% were between 35 and 39 years old; 2.90% between 40 and 44 years; 0.47% were <15 years old; and 0.18% above 45 years. (Mother's education): 55.47% of mothers had completed high school, 22.12% had completed higher education; 19.12% had completed elementary school; 2.84% had completed primary school and 0.46% had no education. (Maternal Marital Situation): 57.28% were single mothers; 37.60% were married; 3.60% had a Common-law marriage; 1.30% were separated or divorced; 0.22% of the mothers were widows.(Number of prenatal consultations): 73.49% performed above 7 consultations; 20.61% performed between 4 to 6 consultations; 4.54% performed between 1 to 3 consultations and 1.36% performed no consultations. (Mother's Gestational Age): 89.90% were between 37 and 41 weeks; 7.84% were between 32 and 36 weeks; 0.90% were between 28 and 31 weeks; 0.81% were above 42 weeks; 0.51% were between 22 to 27 weeks; 0.04% were less than 22 weeks pregnant.(Type of Pregnancy): 97.54% had a single pregnancy; 2.35% had a double pregnancy; 0.11% had triple pregnancy or more (Type of Birth): in relation to the total data of the municipality: 52.55% were born by Cesarean, 47.45% were natural birth. Regarding to the data of (Type of birth per Coordinators): (Cesarean): the highest average, 63.38% of the mothers living in CRS Oeste had Cesarean; 59.11% CRS Southeast; 57.03% CRS Centro; 52.74% CRS Norte; 48.81% CRS Sul; 46.12% CRS East. (Natural birth): 53.88% of the mothers living in CRS Leste had natural birth; 51.19% living in CRS Sul; 47.25% living in CRS Norte; 42.97% living in CRS Centro, 36.61% living in West Zone.(Gender of the Newborn): 51.30% were male and 48.89% were female. (Birth weight): in relation to the total data of the municipality of birth weight, <500g: 0.06%; 500g to 999g: 0.58%; 1000g to 1499g: 0.86%; 1500g to 1999g: 1.78%; 2000g to 2499g: 6.22%; 2500g to 2999g: 25.27%; 3000g to 3499g: 41.74%; 3500g to 3999g: 19.63%; 4000g and +: 3.87%. (Birth Weight per Coordinators with the highest averages): <500g: 0.09% in CRS Centro; 500g to 999g: 0.68% in CRS Sudeste; 1000g to 1499g: 1.03% in CRS Sudeste; 1500g to 1999g: 2.13% CRS West and CRS Southeast; 2000g to 2499g: 29.64% CRS Southeast; 3000g to 3499g: 22.99% in CRS Sudeste; 4000g and +: 4.35% CRS Southeast. (Apgar of 1 min): 86.71% were in the range of 08 to 10 with good vitality; 11.45% were in the range from 04 to 07 with moderate asphyxia; and 1.85% were in the range of 0 to 03 with severe asphyxia. With respect to (Apgar of 5?? min), 97.74% were in the range of 07 to 10 with good vitality, and good adaptation, 1.90% of the newborns were in the range of 04 to 06 with moderate asphyxia and 0, 37% were in the range 0 to 3 with severe asphyxia. About (Congenital Anomaly), 98.90% did not present and 1.10% did. Conclusion: The study of the epidemiological profile of mothers and newborns together with the analysis of the results of the implementation of a specific program strengthens the continuity and the pursuit for the quality and improvement in prenatal, type of birth and postpartum.